POLA PEMBELAJARAN JARAK JAUH PADA PELAJARAN BAHASA ARAB DI SMP MUHAMMADIYAH 8 KEBAKKRAMAT - Ismail Lutfiriyanto; Hakimuddin Salim; Nurul Latifatul Inayati (Universitas Muhammadiyah Surakarta, 2021)
The Indonesian education system that has changed since the Covid-19 outbreak has caused changes in today's educational life. One of the problems that stand out is the inadequacy of distance learning which is currently being felt by the world of education in Indonesia. This distance learning teacher is required to prepare to learn as well and as creatively as possible in providing material. This distance learning process does not only involve teachers and students but also parents are required to be involved in this distance learning process.This study aims (1) to describe the pattern of distance learning towards Arabic lessons at SMP Muhammadiyah 8 Kebakkramat (2) to identify the obstacles found during the pattern being applied to distance learning at SMP Muhammadiyah 8 KebakkramatThis study uses a qualitative descriptive approach, the research subjects are Arabic Language Teacher, Deputy Head of Curriculum, and researchers also conducted research on several students in each class at SMP Muhammadiyah 8 Kebakkramat. The data collection method used in this research is the observation method, the interview method, and the documentation method. Data analysis in this study is qualitative data analysis.The results showed that (1) The pattern of distance learning in Arabic subjects at SMP Muhammadiyah 8 Kebakkramat was carried out remotely using an online learning model. Learning to use applications, namely social media Whatsapp (2) The obstacles that greatly affect the distance learning process at SMP Muhammadiyah 8 Kebakkramat for Arabic subjects are network difficulties and the absence of internet quota.